Birth by caesarean section and semen quality in adulthood: a Danish population-based cohort study - Kun Huang; Anne Gaml-Sørensen; Nis Brix; Andreas Ernst; Linn Håkonsen Arendt; Jens Peter Ellekilde Bonde; Karin Sørig Hougaard; Gunnar Toft; Sandra Søgaard Tøttenborg; Cecilia Høst Ramlau-Hansen (BMC, 2024)
Abstract Background The caesarean section (CS) rate has increased worldwide and there is an increasing public and scientific interest in the potential long-term health consequences for the offspring. CS is related to persistent aberrant microbiota colonization in the offspring, which may negatively interfere with sex hormone homeostasis and thus potentially affect the reproductive health. It remains unknown whether adult sons' semen quality is affected by CS. We hypothesize that CS is associated with lower semen quality. Methods This study was based on the Fetal Programming of Semen Quality cohort (FEPOS, enrolled from 2017 to 2019) nested within the Danish National Birth Cohort (DNBC, enrolled from 1996 to 2002). A total of 5697 adult sons of mothers from the DNBC were invited to the FEPOS cohort, and 1044 young men participated in this study. Information on mode of delivery was extracted from the Danish Medical Birth Registry, and included vaginal delivery, elective CS before labor, emergency CS during labor and unspecified CS. The young men provided a semen sample for analysis of semen volume, sperm concentration, motility and morphology. Negative binomial regression models were applied to examine the association between CS and semen characteristics with estimation of relative differences in percentages with 95% confidence intervals (CIs). Results Among included sons, 132 (13%) were born by CS. We found a slightly lower non-progressive sperm motility (reflecting higher progressive sperm motility) among sons born by CS compared to sons born by vaginal delivery [relative difference (95% CI): − 7.5% (− 14.1% to − 0.4%)]. No differences were observed for other sperm characteristics. When CS was further classified into elective CS, emergency CS and unspecified CS in a sensitivity analysis, no significant differences in non-progressive motility were observed among sons born by any of the three types of CS compared to sons born vaginally. Conclusions This large population-based cohort study found no significant evidence for an adverse effect on semen quality in adult sons born by CS.